Application Semiotics Narrative Greimas About Narration The story of Musa and Khidir - Bilfahmi Putra; Imamul Muttaqin; Toni Markos (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Stories of the prophets occupy important in the Qur’an. Story the meeting of Prophet Musa and Khidir, which displays plot conflict problematic to have elements implied, among other things caused second figure main allegedly to do action controversial. Studying this to find structure accounting reveals essentially the story of Musa and Khidir in the Qur'an based on correlation between patterns and structure narration. Article this uses method qualitative with type study literature with approach analysis semiotics AJ Greimas model narrative. Research results: First, structure the narrative of Musa and Khidir found in QS. Al- Kahf verses 62- 80 consists of six segments that have structure actant. From the whole actant every segment, found actant main; (a) senders: Allah 's command to Musa, (b) subject: Musa, (c) receive: Musa, (d) object: Studying with Khidir, (e) helper: agreement early, (f) opposite: difference paradigm. Structure functional narrative consists of three stages: (1) situation beginning: tell beginning the journey of Musa and his guards, (2) transformation: outlines conflict During study to Khidir, (3) situation ends narrate farewell of Musa and Khidir. Second, through analysis of the structure of the mind, I found a symptom of desire from Musa to do Allah 's command. The conflict happened because there exists a different paradigm epistemological Among both.